Student Selection Process and Co-Financing as School Segregation Factors: Three Case Studies [Selección de Alumnos y Co-Pago Como Factores de Segregación Escolar: Presentación de Tres Casos de Estudio] - Cordoba-Calquin, C (Pontificia Universidad Catolica de Valparaiso, 2016)
Socio-economic segregation at school is a phenomenon that has been getting increasing attention in our country. The specialized literature indicates that there are three types of factors that may have an influence on it: Residential segregation, socio-cultural factors and institutional factors. We present the results of an on-going research on elementary education. We analyze segregation at school focusing on territorial communities known as Geographically Enclosed Units, in which schools tend to be within the same enclosure. We chose a mixed qualitative and quantitative approach. We present three case studies from a comparative perspective: In all cases there is one municipal school and one subsidized private school. The analysis indicates that socio-economic segregation observed may be explained basically in terms of selection and co-financing practices.